Fast WAT Test Structure for Measuring Vt Variance Based on Latch-based Comparators - Lee, Kao-Chi; Wu, Kai-Chiang; Tsai, Chih-Ying; Chao, Mango Chia-Tso (My University, 2017)
As the technology of IC manufacturing continually scales down, process variations become more and more crucial than before. To statistically characterize local process variations, the traditional array-based test structure measures threshold voltage (Vt) for a sufficiently large number of devices-undertest (DUTs). However, the array-based test structure requires long time for DUT-by-DUT measurement; furthermore, it suffers from significant IR drop or leakage current due to the large number of DUTs, which results in the loss of measurement accuracy. In this paper, we present a novel sense-amplifierbased test structure that can monitor process variations based on rapid characterization of Vt variance, with marginal error of accuracy. A test-chip containing 120 NMOS and 120 PMOS DUTs has been implemented in 28nm CMOS process technology. Various experiments reveal promising efficiency and accuracy of the proposed test structure, for characterizing Vt variance.